Transgenic mice Cre-dependently expressing mutant polymerase-gamma: novel test-system for pharmacological study of mitoprotective drugs - Marina V. Kubekina; Yulia Yu. Silaeva; Alexandra V. Bruter; Diana S. Korshunova; Leonid A. Ilchuk; Yulia D. Okulova; Mariya O. Soldatova; Evgeniya Seryogina; Inga M. Kolesnik; Polina A. Ukolova; Mikhail V. Korokin; Alexey V. Deykin (Belgorod National Research University, 2021)
Introduction: PolG-alpha is a nuclear-encoded enzyme which provides replication and repair of mitochondrial DNA. D257A mutation of PolG-alpha leads to change in the N-terminal "proofreading" domain, which deprives the enzyme of 3'-5' exonuclease activity, resulting in accumulation of mutations in the mitochondrial genome. Materials and methods: Murine zygotes were microinjected with transgene construction carrying mutant murine Polg coding sequence and GFP coding sequence by a loxP-flanked STOP-cassette. Two Cre-activator strains, CMV-Cre (systemic activation) and Tie2-Cre (endothelial activation), were used for activation of the transgene. To confirm the insertion and Cre-dependent activation of the transgene, genotyping and qPCR copy number measurement of mutant Polg were performed, and GFP fluorescence was assessed. Results: Two primary transgenic animals were used as the founders for two lines with copy numbers of transgene ~7 and ~5. After systemic activation, the number of the transgene copies decreases to ~1.0 while endothelial specific activation does not affect the number of transgene copies in tail tissue. Discussion: A murine model with spatial control of mutant Polg expression has been developed. To our knowledge, this is the first transgenic model of tissue-specific mitochondrial dysfunction. Conclusion: Transgenic mice Cre-dependent expressing mutant polymerase-gamma are a novel test-system for studying mitochondrial biology and efficacy of mitoprotective drugs.